Organizational spiritualities: An ideology-based typology - Cunha, Miguel Pina e (2012)
The topic of spirituality is gaining an increasing visibility in organizational studies. It is the authors contention that every theory of organization has explicit or implicit views of spirituality in the workplace. To analyze the presence of spiritual ideologies in management theories, they depart from Barley and Kunda’s Administrative Science Quarterly article and analyze management theories as spirituality theories with regard to representations of people and the organization. From this analysis, we extract two major dimensions of people (as dependent or independent workers) and the organization (as spiritually informed or spiritually uninformed) that, in combination, result in a typology that advances four organizational types of spirituality: the soulful organization, the holistic organization, the ascetic organization, and the professional organization. The expression of spirituality in each of these forms is discussed with the aim of contributing to a critically informed analysis of organizational spirituality.